Geography, poverty and development: An interdisciplinary debate / Geografi a, pobreza e desenvolvimento: um debate interdisciplinar - Anand Prasad Mishra (Sociedade & Natureza)
n emerging feature of contemporary development studies in India is the deployment of an interdisciplinary approach involving geographical location, level of poverty, nature of development and planning etc. The prevalence of poverty in a specifi c geographical location represents the evolving pattern of deprivation under a particular mode of production. The historicity of poverty in a geographical spaceneeds an independent enquiry and identifi cation of different production systems which are responsible for the problem of deprivation through multiple routes. The present paper is an attempt to initiate a debate on the issue of poverty, especially in a tribal region, through a multi-dimensional perspective, i.e. interrelation between geography, poverty, development and planning. The paper identifi es one of the most poverty-stricken regions of India for a detailed discussion of the various casual factors which are apparently responsible for the poverty of that region. The paper also tries to explore the historical background of poverty in the study area (Babhani Block of Sonbhadra U. P.).